Western Flyer after being pulled from the water. - John Gregg:::Photographer:::::::::::: (Port Townsend, Washington)
The Western Flyer sits in dry dock after being pulled from the water and before restoration by the Port Townsend Shipwrights Cooperative. Steinbeck and Ricketts chartered the Western Flyer in 1940 for their expedition to the Sea of Cortez.